The Archetype of the Dying and Rising God in World Mythology - Rovang, Paul (Lexington Books, 2023)
The Archetype of the Dying and Rising God in World Mythology is the first global treatment of the dying and rising god archetype since that classification was called into serious doubt in the final decades of the twentieth century. While assaults on the concept have focused on the Classical and ancient Near Eastern (Biblical) traditions, this study goes beyond but also includes these areas to encompass world mythology. Beginning with an interrogation of the most influential criticisms, the author then examines evidence for the archetype's validity by analyzing dying and rising god myths from ancient Near Eastern, Classical, and non-Classical sources from around the world. He treats implications of the archetype for religious studies, literature, and psychology, both in discussing the myths themselves and in separate chapters dedicated to these fields. The focused treatment on single myths makes this book a useful reference source. At the same time, its inductive approach to evidence provides a conclusive argument on the question with applications that warrant reading it from cover to cover. Additional distinctive features of this book include a thematic interpretation of T. S. Eliot's Waste Land, a new perspective on the Jungian archetypes, and a call for a neo-archetypal approach to literary criticism.